Experimental Study of Flame Acceleration Processes and Deflagration-to-Detonation Transition: Review of Works of the A.V. Luikov Heat and Mass Transfer Institute of the National Academy of Sciences of Belarus - Krivosheyev, P. N.; Kuzmitski, V. V.; Penyazkov, O. G. (Combustion, explosion, and shock waves, 2023)
This paper is a brief review and systematization of studies of flame acceleration and deflagration-to-detonation transition in circular smooth pipes, performed during the last several years at the A. V. Luikov Heat and Mass Transfer Institute of the National Academy of Sciences of Belarus. All stages of the flame acceleration process from initiation with a weak source to detonation are demonstrated and described.